PENGARUH PENERAPAN METODE MIND MAPPING TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD NEGERI LIMBUNG PUTERA KECAMATAN BAJENG KABUPATEN GOWA - Muhammad Taufiq; Fitriana HS, Eka; Amaliyah, Nurhadifah; Fatimah, Waddi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the mind mapping method on student learning outcomes in social studies class V of Limbung Putera Public Elementary School, Bajeng District, Labupaten, Gowa. This study is a quantitative study with a pre-experimental form with a one group pretest-posttest design. The sample in this study were 28 fifth grade students consisting of 13 male students and 15 female students. The sampling technique in this study was purposive sampling. The research instruments used were teacher observation sheets, student observations, learning outcome tests, student responses, and documentation. Data analysis used descriptive analysis and inferential statistics with the help of the SPSS 21 computer program. The results of this study indicate that the teacher's ability to apply the mind mapping method obtained an average of 3.6, which means it was implemented well. The learning outcomes of fifth grade students are described from the prerequisite test consisting of the results of the pretest normality test 0.60 ≥ 0.05 and posttest 0.82 ≥ 0.05 normally distributed, homogeneous test results and hypothesis test results 0.000 with the criteria sig. (0.000) ≥ a (0.05). So, the results of this study indicate that there is an influence of the mind mapping method on student learning outcomes in the fifthgrade social studies lesson at Limbung Putera Public Elementary School, Bajeng District, Gowa Regency.